The power of agricultural productivity: A pathway to poverty reduction - Lenaerts, Bert; Balié, Jean (CGIAR Impact Platform on Poverty Reduction, Livelihoods and Jobs, 2024)
Agricultural productivity is a cornerstone of economic development and a critical factor in the fight against poverty. When we discuss improving agricultural output, we aren’t just looking at statistics; we’re aiming to propose a conceptual as well as practical framework that can significantly impact real lives and help lift communities out of poverty.